Mesco dux Polonie baptizatur – the Access of the Piast Power to the Respublica Christiana - Dobosz, Józef (Poznańskie Studia Slawistyczne, 2016)
The article refers to the religious and cultural turning point that took place in the Piast state due to the act of accepting Christianity by the prince Mieszko I (who died in 992) in 966. These issues are presented from the view-point of a controversial interpretation regarding the source foundation and literature, number of which has increased over the decades. The baptism of the historically first Polish ruler was preceded by his marriage with the Czech princess Dobrava (who died in 977), which resulted in the alliance with the Přemyslid monarchy and in the growing connections with Germany along with the conflicts with the Veleti. The consequence of the 966 year’s events was the initiating of the Christianization processes in the whole state of the Piasts and its gradual accessing to the circle of Latin culture. In effect, the grounds for the institutional Church were formed, and the Polish aspirations for being a member of Western culture, which have lasted for all the centuries, were established.